Textual ecologies in Islam: improvising the perfect Qur'an in Calligraphy - Senay, Banu (Journal of religious and political practice, 2017)
The focus of this paper is a significant Islamic skilled practice, hat (calligraphy), the art of beautiful writing with the reed pen. In Islam shaping God's very words through calligraphic writing is both an act of worship as well as an art form. In this paper I briefly explore how the act of writing the Qur'an is a means through which the performative power of the text is reproduced. To clarify what is meant here by the performative power of the Qur'an, the paper first sketches out some of the key propositions made by Muslim scholars who claim that the Qur'an loses its perfect status when translated into another language. Secondly, based on fieldwork observations at a Muslim arts studio in Istanbul, I discuss how calligraphy enables its skilled practitioners ways of engaging with the Qur'an that involves a continuous re-interpreting, re-composing, and re-performing of the Divine Word.